2006
DOI: 10.1093/molehr/gal073
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro model of human placental trophoblast deportation/shedding

Abstract: Deportation of trophoblast shed from the placenta into the maternal circulation was first described over 100 years ago. Despite this, little is known about the quantity or nature of the shed and deported trophoblasts. Neither do we have a clear understanding of the fate of deported trophoblasts nor do we have a clear understanding of their effects on the maternal physiology. This deficiency is largely due to the inaccessibility of deported trophoblasts in vivo. This study aimed to produce a model that would al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…Both methods are widely used [20,23,41,42]. It has previously shown that the syncytiotrophoblast undergoes significant artefactual degradation during the first 24 h of villous explant culture [43]. By 72h of culture, the underlying cytotrophoblast have fused to form a new syncytium that has formed under the syncytium in vitro [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both methods are widely used [20,23,41,42]. It has previously shown that the syncytiotrophoblast undergoes significant artefactual degradation during the first 24 h of villous explant culture [43]. By 72h of culture, the underlying cytotrophoblast have fused to form a new syncytium that has formed under the syncytium in vitro [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…It has previously shown that the syncytiotrophoblast undergoes significant artefactual degradation during the first 24 h of villous explant culture [43]. By 72h of culture, the underlying cytotrophoblast have fused to form a new syncytium that has formed under the syncytium in vitro [43,44]. This may explain that Redman et al who only cultured 24h in their explant culture model or used a short term perfusion model to isolate STBM, where the syncytium would have been more representative of that present in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] . A , B Optical sections obtained by confocal microscopy demonstrating examples of SNAs shed from non-stained placental explants.…”
Section: Discussionmentioning
confidence: 99%
“…Placental explants were cultured overnight following an established in vitro model [29] . Trophoblast debris was collected and transferred into 100 × 20 mm BD Optilux TM petri dishes (Becton Dickinson, Auckland, New Zealand) and visualised using either an ELWD 0.3 (Nikon, Auckland, New Zealand) or an Eclipse Ti 50 microscope (Nikon).…”
Section: Isolation Of Snas From Placental Explantsmentioning
confidence: 99%